Rekayasa Teknologi Pengelupas Kulit Ari Kedelai dalam Efisiensi Produksi Keripik Tempe Sagu pada Industri Kecil Menengah di Kabupaten Bantul - Nugroho, Sumantri Sri; Baskoro, Bernardus Bayu (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2021)
Poverty is the main problem in Indonesia. The Special Region of Yogyakarta, where the poverty rate is above 10 percent, tries to reduce it. One of the solutions is by issuing a policy on the local government budget for 2018-2023, which aims to prevent sustainable poverty. The Special Region of Yogyakarta has small-medium industries with their potential resources. These industries are supposed to be the dominant driver of economies. It is because of their role in absorbing much labor. The use of technology and the empowerment of small-medium industries are supposed to support declining the poverty rate in the Special Region of Yogyakarta. The appropriate use of technology is Applied Engineering Technology. The entrepreneurs of sago Tempe chips, which brand is “RAOS”, are equipped with this facilities. The implementation of the machine or tool made is a soybean husks peeler machine. The purpose of making the tool or machine is the production efficiency (purchasing soybean raw material). The stages of the process are carried out from the identification of technical specifications, design, production, and trial of both function and capacity of the tool or machine. Recent trial shows that two times husks peeling process using combination of input or hopper width settings of each process had most efficient result. The husks peeling process need 10 minutes of average time with 97% husks peeled success rate. The conclusions that can be drawn from the activities are: 1) Entrepreneurs can operate the tool or machine properly; 2) Safer tool or machine; 3) The cost of peeling the soybeans is Rp150,00 each kilogram; 4) The production capacity of the tool or machine is 60 kg/hour; 5) Entrepreneurs obtain the efficiency of the cost production.